Enyo up and running - Sutton, Roy (O'Reilly Media, 2015)
With this revised and expanded edition, Enyo contributor Roy Sutton gets you started with the framework's core object-oriented features, including its modular design, reusable and extensible components, layout and widget libraries, easy-to-use deployment options, and support for HTML5 standards.